Real-world outcomes of observation and treatment in diabetic macular edema with very good visual acuity: the OBTAIN study - Catharina Busch (2019)
© 2019, The Author(s). Aims: To describe and compare the functional and anatomical outcomes of untreated and treated diabetic macular edema (DME) in eyes with very good baseline visual acuity (VA) in a real-world setting. Methods: A 12-month, retrospective, multicenter, observational cohort study, including DME patients with baseline visual acuity (VA) ≤ 0.1 logMAR (≥ 20/25 Snellen) and central subfield thickness (CST) > 250 µm with intra- and/or subretinal fluid seen on optical coherence tomography. Results: A total of 249 eyes were included, of which 155 were treated and 94 were non-treated during follow-up. Most eyes maintained vision (VA gain or VA loss < 5 letters) at 12 months (treated: 58.1%; non-treated: 73.4%). In non-treated eyes with stable VA within the first 6 months, VA was maintained throughout the follow-up in most cases (86.3%). In non-treated eyes with VA loss ≥ 5 letters within 6 months (36.7%), further observation led to worse visual outcome than treatment (− 4.2 vs. − 7.8 letters, p = 0.013). In eyes in which treatment was initiated at baseline (n = 102), treatment with 8–12 anti-VEGF injections led to better visual outcome compared to treatment with less injections (− 0.3 ± 3.6 letters vs. − 3.8 ± 6.2 letters, p = 0.003). Conclusion: In a real-world setting, the majority of DME patients with very good VA maintained vision at 12 months, regardless of whether the DME was treated or not. This study supports close observation of eyes with DME and very good VA with consideration of treatment when a one line drop in vision is observed.